The politics of attack : Communiqués and insurrectionary violence - Loadenthal, Michael (Book collections on Project MUSE., 2017)
This story explores the history, ideas, and strategies of insurrectionary anarchism. This book asks the reader to consider the theories of bomb-throwing, window-smashing, graffiti-scrawling arsonists, and through an examination of movement communiques, embrace the critique offered by the clandestine, urban guerrillas fighting for total liberation against the omnipresent forces of violence and coercion.